QUALITY ASSESSMENT OF DENTAL IMPLANTS UNDER ASPECTS OF SEM AND EDX ANALYSIS - A COMPARISON OF FIVE ONE-PIECE IMPLANTS - Dirk U. Duddeck DDS (Romanian Society of Oral Rehabilitation, 2016)
Dental implants are supposed to be clean, when delivered in a sterile packaging. Implant surface pollution with organic particles and/or major inorganic residues originating from the production process are suspected to cause insufficient or missing osseointegration of dental implants. Unintended micrometer-scale particles may induce a foreign body reaction with a loss of bone in the early stages of osseointegration. In cooperation with the University of Cologne and the Charité University Medicine Berlin the Medical Materials Research Institute Berlin analyzed the quality of dental implants in three consecutive studies since 2008 [1, 2]. In 2015 extensive material contrast images were obtained and qualitative and quantitative elemental analyses were performed on 135 dental implants using the same study protocol. Results of the recent study and comparison with previous analyses showed an increasing spread of quality in the market. Dental implants are an integral part of the therapeutic armamentarium of contemporary dental practices. With their excellent success rates, they have become the globally established treatment alternative to purely prosthetic solutions for tooth loss. And with the variety of implant systems offered, it has become ever more difficult for the dentist to choose just the right system for his or her practice and patients. Specific surface topographies, material properties that promote osseointegration or surface treatments are often emphasized in advertising as significant advantages to distinguish a given system from its many competitors